Positron emission tomography in Alzheimer''s disease: early prediction and differentiation. (January 2009) - Mistur, Rachel; Mosconi, Lisa; De Santi, Susan; Li, Yi; Tsui, Wai; de Leon, Mony
The development of biomarkers for the preclinical detection of neurodegenerative diseases such as Alzheimer''s disease (AD) is a vital step in developing prevention therapies. One consistent feature of AD is a reduction in the cerebral metabolic rate of glucose (CMRglc), a measure of neuronal function. In vivo brain 2-[18F]fluoro-2-deoxy-D -glucose-PET imaging demonstrates consistent and progressive CMRglc reductions in AD patients, the extent and topography of which correlate with symptom severity. There is increasing evidence that CMRglc reductions occur at the preclinical stages of AD and predict decline years in advance of clinical symptoms. This review will give an overview of FDG-PET results in individuals at risk for developing dementia, including: presymptomatic individuals carrying mutations responsible for early-onset familial AD; patients with mild cognitive impairment, often a prodrome to late-onset sporadic AD; nondemented carriers of the ApoE εε4 allele, a strong genetic risk factor for late-onset AD; cognitively normal subjects with a family history of AD; subjects with subjective memory complaints; and normal elderly who were followed longitudinally until they expressed the clinical symptoms and later received postmortem confirmation of AD. We will then review the most recent studies using FDG-PET as an early differential diagnostic tool in AD.